ANALISIS PENERAPAN HYBRID WORKING DALAM MENINGKATKAN PRODUKTIVITAS KERJA PEGAWAI PADA DINAS KOPERASI & UMKM PROVINSI SULAWESI TENGGARA - Darpin; Taufik; Muhammad Fikran (Journal Publicuho, 2022)
This study aims to find out how the application of hybrid working in increasing employee work productivity. The method used in this study is a type of qualitative research with case studies at the Dinas Koperasi, Usaha Mikro Kecil dan Menengah (UMKM) of Southeast Sulawesi Province. The data collection techniques used in this study were observation, interview and documentation. Data analysis techniques through data reduction, data presentation, and drawing conclusions. The results showed that the application of hybrid working runs optimally and has a good impact on employee work productivity. This can be seen from several factors that support the implementation of the hybrid work concept such as the availability of infrastructure and technology is enough to do digital-based work. The work productivity of employees during the implementation of hybrid working is also good which can be seen from the aspects of knowledge, skills, abilities and attitudes that employees have are also very good. Employees are able to adapt when work that is usually done conventionally must be done online or virtually. By using digital-based infrastructure, employees can work effectively and efficiently, so the results of this study show that employees can adapt and be able to work well during the implementation of hybrid working.